y=(7x+9)(x-1)

Simple and best practice solution for y=(7x+9)(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(7x+9)(x-1) equation:


Simplifying
y = (7x + 9)(x + -1)

Reorder the terms:
y = (9 + 7x)(x + -1)

Reorder the terms:
y = (9 + 7x)(-1 + x)

Multiply (9 + 7x) * (-1 + x)
y = (9(-1 + x) + 7x * (-1 + x))
y = ((-1 * 9 + x * 9) + 7x * (-1 + x))
y = ((-9 + 9x) + 7x * (-1 + x))
y = (-9 + 9x + (-1 * 7x + x * 7x))
y = (-9 + 9x + (-7x + 7x2))

Combine like terms: 9x + -7x = 2x
y = (-9 + 2x + 7x2)

Solving
y = -9 + 2x + 7x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -9 + 2x + 7x2

See similar equations:

| 105=-3x+5(-3x+3) | | 7m-3m+4=16 | | 5lnx=30 | | 18y=12-12x | | =2500-2x | | 7x-6=3(x^6) | | (12x+10)-(-4x-6x+10)= | | 6[-6x+6+4x(x+1)]=6x+2 | | 0.5x+0.25=x | | 3x+3(5x-10)=138 | | (2mn+8m^2n-5n+6m)= | | 0=(t-20)+(t-400) | | 8.57x+17.14=34.28 | | t-20=t-400 | | (2mn+8m^2n-5n+6m)(10mn^2)= | | 3cos(x)=8-4sec(x) | | Y=2500-2x | | 10x+4x+4+9=4x+3+9x | | x^2+4x=47 | | 3.91x+16=15.2881+4x | | 3cosx=8-4secx | | v^2=18v | | -5(4b+4)+(21b-7)=0 | | R^2-4r-6=0 | | (x^2-10x)+(y^2-6y)=-33 | | y(-2)=-6.8(-2)+5 | | 3x+4(2x-12)=73 | | 5y+18y-(-2y)+(-10y)= | | 0.12=0.5y | | 0.12=0.5 | | 5m-7=12 | | 4p-8p=16 |

Equations solver categories